The Psychometric Properties of the Norwegian version of Youth Level of Service/Case Management Inventory (YLS/CMI) - Jakobsen, Reidar; Kornør, Hege (PsykTestBarn, 2017)
Description: Youth Level of Service/Case Management Inventory (YLS/CMI) was developed in the 1990’s by the Canadian researchers Andrews and Hoge. YLS/CMI is an assessment tool designed to assess risk and identify treatment targets among young offenders (12-17 years). The YLS/CMI helps identify the youth’s major needs, strengths, barriers, and incentives, and to select the goals for him or her in an effective case management. In Norway YLS/CMI are implemented by Bufetat to assess all youth placed in institutions for drug- or conduct problems. YLS/CMI consists of 42 questions, divided into eight subscales and one total score. The inventory is a professional completed semi-structured interview (administration time 30-40 minutes). All rights are reserved by Multi Health Systems Inc, North Tonawanda, NY, US. Literature search: Our systematic literature search for evidence for the psychometric properties of the Scandinavian versions of YLS/CMI identified no relevant publications. We identified and included one study that reported means scores in three child welfare samples. Conclusion: No evidence for the psychometric properties of the Norwegian version of YLS/CMI is available. There is therefore a need for psychometric studies.